Assertiveness Measurement Tools Development In Assessing Assertive Behavior In Eviction Victims In Jakarta - Hasyim Asy’ari; Zakiyus Shadicky; Grista Ananda Damanik; Irena Nova Wijaya (Syntax Corporation Indonesia, 2024)
Evictions as a social phenomenon have several negative impacts on the community, such as not only losing their homes but also affecting jobs, daily livelihoods, children's schools, women and social impacts such as losing long- established kinships. Evictions on a large scale accompanied by inappropriate relocation programs will cause economic and socio-cultural impoverishment for the community, which also leaves a traumatic impact. In the legal aspect, evictions can also result in violations of the basic rights of their own citizens. The purpose of this study is to develop a psychological measurement tool in assessing assertive behavior in eviction victims in DKI Jakarta. The measuring instrument was developed based on Jakubowski and Lange's (1978) assertiveness construct. After testing its validity and reliability, this assertiveness measuring instrument has a high reliability and validity coefficient because it is close to 1. In testing the validity, only a few statement items are invalid, and there are some items that are discarded because they do not have a standard t-value of 1.96, as well as a loading factor that also does not exceed the expected value. This is possible because the dimensions in assertiveness are indeed dimensions that really measure individual assertiveness.